2015
DOI: 10.7860/jcdr/2014/10545.5424
|View full text |Cite
|
Sign up to set email alerts
|

Blastic Phase of CML with Microfilaria: A Rare Case Report

Abstract: A 37-year-old male, diagnosed case of CML on Imatinib mesylate, presented with low grade fever, weight loss and abdominal distension for one month. Physical examination revealed massive splenomegaly and hepatomegaly, however there was no lymphadenopathy.His hemoglobin was 10.5 g/dl, total leucocyte count was 52.31 x 109 / L with platelet count of 30 x 109/L. Differential leucocyte count on peripheral smear showed 21% blasts [Table/ Fig-1], 30% polymorphs, 16% lymphocytes, 1% myelocyte, 1%metamyelocyte, 30%mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Uzma Zafar et al (8) reported an interesting case of low back pain and destruction of first lumbar vertebra by the microfilariae residing in the bone marrow. There were several case reports of huge splenomegaly in leukaemia patients with incidental detection of bone marrow microfilariae (9)(10)(11). Possible explanation for splenomegaly in those cases were due to leukaemia not filariasis because spleen is usually not involved in filariasis except in some experimentally infected animals although Schuurkamp GJ et al (14) showed occurrence of filarial splenomegaly in their articles.…”
Section: Discussionmentioning
confidence: 99%
“…Uzma Zafar et al (8) reported an interesting case of low back pain and destruction of first lumbar vertebra by the microfilariae residing in the bone marrow. There were several case reports of huge splenomegaly in leukaemia patients with incidental detection of bone marrow microfilariae (9)(10)(11). Possible explanation for splenomegaly in those cases were due to leukaemia not filariasis because spleen is usually not involved in filariasis except in some experimentally infected animals although Schuurkamp GJ et al (14) showed occurrence of filarial splenomegaly in their articles.…”
Section: Discussionmentioning
confidence: 99%
“…Splenomegaly is an uncommon presentation. Where leukaemia is present, microfilariae may be an incidental and co-existing finding, 57 However in those cases, splenomegaly was due to the leukaemic process.…”
Section: Discussionmentioning
confidence: 99%
“…Prior reports of filariasis described on bone marrow aspirate have often been associated with underlying leukemia, 57 and sometimes with non-neoplastic progressive splenomegaly and anaemia, 8 resulting from inadequate management of peripheral blood eosinophilia.…”
Section: Introductionmentioning
confidence: 99%